2016
DOI: 10.1016/j.acap.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Grit: A Potential Protective Factor Against Substance Use and Other Risk Behaviors Among Latino Adolescents

Abstract: Purpose Grit, defined as “working strenuously toward challenges, maintaining effort and interest over years despite failure, adversity, and plateaus in progress,” is strongly associated with academic achievement and life success and may also be associated with health outcomes and behaviors. We examined predictors of grit, and the association between grit and health behaviors among at-risk Latino adolescents. Methods We analyzed baseline survey data collected in 2013-2014 from a sample of 1,270 9th graders in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 30 publications
2
54
1
2
Order By: Relevance
“…The grit's promising influences are not limited to academic context among university students. An ample body of empirical evidences articulated that grit positively correlated with meaning in life (Kleiman et al, 2013), higher levels of well-being (Salles et al, 2014), constructive coping mechanisms (Fillmore, 2015), and lower odds of delinquent behavior (e.g., alcohol use, marijuana use, and fighting level; Guerrero et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grit's promising influences are not limited to academic context among university students. An ample body of empirical evidences articulated that grit positively correlated with meaning in life (Kleiman et al, 2013), higher levels of well-being (Salles et al, 2014), constructive coping mechanisms (Fillmore, 2015), and lower odds of delinquent behavior (e.g., alcohol use, marijuana use, and fighting level; Guerrero et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Related to the personal outcomes, the literature has found that grit predicted several variables. For instance, grit positively correlated with physical exercises (Reed, 2014), meaning in life (Kleiman, Adams, Kashdan, & Riskind, 2013), higher levels of well-being (Datu et al, 2016;Salles, Cohen, & Mueller, 2014), resilience and constructive coping mechanism (Fillmore, 2015), fewer career changes and a lower rate of watching television (Duckworth & Quinn, 2009), lower odds of alcohol use, marijuana use, fighting level and lower involvement in delinquent behavior (Guerrero, Chung, Dosanjh, & Wong, 2016). Furthermore, grit correlated with participants' profile of mood states, self-control and the personality (Nishikawa et al, 2015).…”
Section: Gritmentioning
confidence: 99%
“…(Cullen et al 2006;Sanbonmatsu et al 2006) Procedure For this study, we analyzed data from the Reducing Inequities through Social and Educational change follow-up (RISE Up) Study, which is a longitudinal natural experimental study that was originally designed to examine the impact of attending a high performing public school on risky health behaviors. Additional details of the original study design and sampling are provided elsewhere (Dudovitz et al 2018;Guerrero et al 2016). The human subjects research review board approved all research activities (IRB#16-001512).…”
Section: Participantsmentioning
confidence: 99%
“…While much of the work examining grit has focused on academic outcomes, a burgeoning literature has begun to highlight its relevance to health-related behaviors and mental health outcomes. Those higher in grit are less likely to have mental health issues such as anxiety, depression, and substance abuse (Guerrero et al, 2016;Maddi, et al, 2013;Musumari et al, 2018). Adolescents with higher levels of grit are less likely to engage in alcohol or marijuana use or to engage in delinquent behaviors (Guerrero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Those higher in grit are less likely to have mental health issues such as anxiety, depression, and substance abuse (Guerrero et al, 2016;Maddi, et al, 2013;Musumari et al, 2018). Adolescents with higher levels of grit are less likely to engage in alcohol or marijuana use or to engage in delinquent behaviors (Guerrero et al, 2016). For those at especially high risk of psychopathology, grit may, therefore, be an important mitigating factor against poor mental health outcomes, such as SU.…”
Section: Introductionmentioning
confidence: 99%